MORPHOLOGICAL, PHYSICAL, AND CHEMICAL CHARACTERISTICS OF SOME VOLCANIC SOILS OF MT. GALUNGGUNG - Budi Mulyanto (Jurnal Ilmu Tanah dan Lingkungan, 1999)
Results of the study on morphological, physical, and chemical characteristics of three pedons developed on volcanic materials of Mt. Galunggung, namely BM1, 8M2, and 8M3, showed that these pedons had a different stage of profile development. Pedon BM1 is classified as undeveloped, 8M2 is medium developed, and 8M3 is strongly developed. This is mainly caused by differences in the relative age of the parent rocks and elevation. Although classified as undeveloped, the soil represented by pedon BM1, the youngest, has immediately been used by farmers for rice cultivation because of water abundance, and high availability of P, and basic cations derived from weathering of easily weathered amorphous materials and minerals. According to the Soil Taxonomy system of the USDA (Soil Survey Staff, 1996), pedons 8M1, 8M2, and 8M3 are classified as Typic Udipsamment, Taptho Hapludandic Typic Troporthent, and humic Hapludult, respectively. Whilst, according to the FAO/UNESCO system (1988), these pedons are classified as Eutric Regoso/, Eutric Regosol and Humic Aliso/, respectively.